Implementation of OBE in engineering education: Are we there yet? - Sher Mohamad I.A.A. (2023)
In June 2009, Malaysia was admitted as a full member of the Washington Accord, thus signifying that our accreditation process and engineering education system is in full compliance with the provisions of the Accord, including the outcome based approach to education. This paper attempts to discover the real meaning of Outcome Based Education, its origins, and various attempts at implementation. Finally, the current status of OBE implementation in Malaysian engineering programs is reviewed.